MACRO STABILITY AND FINANCIAL STRUCTURE AS THE ROOT CAUSES OF PROBLEMATIC FINANCING OF PROFIT-SHARING PRODUCTS OF ISLAMIC BANKS - Mardianto, Dedi; Sumarlin, Sumarlin; Abdullah, Wahyuddin (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the effect of inflation, capital adequacy and third party funds on problematic financing of production sharing contract products using time series data from January 2015 to December 2021 sourced from the financial services authority (OJK). The research method uses a quantitative approach assisted by the statistical software JASP (Jeffrey's Amazing Statistics Program). The results show that inflation does not have a significant effect, but the capital adequacy variable has a significant negative effect while third party funds have a significant positive effect on problem financing of profit sharing contract products at Islamic banks in Indonesia.